The Contextual Qur’anic Interpretation of Jihad - Kumala, Nur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
In the 20th century, Indonesia was faced with issues of right-wing extremism in the name of religion which affected the benefit of the people. Several acts of terror, the discourse of the caliphate, returning to the sunnah, and dictation of takfiri have become the center of topics in our country, where the issue of